Nanotailored hyaluronic acid modified methylcellulose as an injectable scaffold with enhanced physico-rheological and biological aspects. (1st June 2020) - Das, Beauty; Basu, Arijita; Maji, Somnath; Dutta, Koushik; Dewan, Mitali; Adhikary, Arghya; Maiti, Tapas Kumar; Chattopadhyay, Dipankar
Graphical abstract: Highlights: Novel scaffold was fabricated using nanosized hyaluronic acid and methylcellulose. Nano-hyaluronic acid significantly improved the properties of injectable scaffold. Nano-HA creditably reduce the requirement of high salt content for gelation. It has bestowed better gel strength, physico-rheological and biological properties. It has enhanced actin polymerization and tissue healing at bio-interface. Abstract: The collaborative endeavor in tissue engineering is to fabricate a bio-mimetic extracellular matrix to assist tissue regeneration. Thus, a novel injectable tissue scaffold was fabricated by exploring nanotailored hyaluronic acid (nHA) and methylcellulose (MC) (nHAMC) along with pristine HA based MC scaffold (HAMC). nHA with particle size ∼22 ± 5.3 nm were obtained and nHAMC displayed a honeycomb-like 3D microporous architecture. Nano-HA bestowed better gel strength, physico-rheological and biological properties than HA. It creditably reduced the high content of salt to reduce the gelation temperature of MC. The properties ameliorated with increased in-corporation of nano-HA. The addition of salt showed more prominent effect on gelation temperature of nHAMC than in HAMC; and salting-out effect was dependent on nHA/HA content. Biocompatible nHAMC assisted adequate cell adherence and proliferation with more extended protrusions with better migration rate than control. Thus, biomodulatory effect of nanotailored glycosaminoglycan could be asserted to design an efficient thermo-responsive scaffold.